Pengaruh Regulasi Diri dan Manajemen Waktu terhadap Prokrastinasi Akademik pada Mahasiswa Aktif Organisasi Fakultas Psikologi dan Ilmu Pendidikan Universitas Muhammadiyah Sidoarjo - Dea Noviyanti; Dwi Nastiti (Pusat Riset dan Inovasi Nasional, 2026)
Active involvement in campus organizations requires students to manage academic responsibilities alongside organizational commitments. In practice, this dual role often creates challenges in self-control and time use, which can lead to delays in completing academic tasks. This situation underlies the need to examine how self-regulation and time management are related to academic procrastination among students who are actively engaged in organizations at the Faculty of Psychology and Educational Sciences, Universitas Muhammadiyah Sidoarjo. The research employed a quantitative approach with a correlational design. The population consisted of 340 students who were actively involved in campus organizations, while a sample of 180 students was determined using the Isaac and Michael table with a 5% margin of error and selected through a simple random sampling technique. Data were collected using self-regulation, time management, and academic procrastination scales. The collected data were analyzed using multiple linear regression analysis. The results showed that self-regulation and time management simultaneously had a significant effect on academic procrastination. Partially, self-regulation had a negative and significant effect on academic procrastination, indicating that better self-regulation is associated with lower levels of academic procrastination. In addition, time management also had a negative and significant effect on academic procrastination, suggesting that students who are better at managing their time tend to show lower tendencies toward academic procrastination. These findings highlight the importance of self-regulation and effective time management in minimizing academic procrastination among students who are actively involved in campus organizations.